Assessment of the utilization of modern agricultural machinery in rice production and its problems: A case from San Leonardo, Philippines - S. De Jesus, Fhrizz; Mae Ibarra, Lyka; Agustin, Noel; Anne Murillo, Lady; Leyesa, Marlon (Edelweiss Applied Science and Technology, 2024)
This study examines the relationship between the utilization of modern agricultural machinery and the business technical aspect of rice production of paddy field farmers in San Leonardo, Nueva Ecija, Philippines. The objective of this study is to assess the effectiveness of modern machinery on the business technical aspect of the farmers and the paddy field owners. The study utilized descriptive analysis to assess the use of modern agricultural machinery in rice production and its problems. The design was quantitative, using percentage, frequencies, and weighted mean. The results revealed that the majority of respondents have been operating for 11 to 20 years, owned 1 hectare of land that cultivate 2 times a year and harvest 86 rice sacks per hectare. Rice cultivation is happened during wet and dry season. To maximizing the land, farmers can try other crops while waiting for the season of rice cultivation. In agricultural mechanization, it concluded that plowing machines helps remove clods from the soil, transplanting rice seedlings and applying chemicals using machine can saves time. Harvester machine is suitable in small and large farmland for harvesting and may help farmers to save time, effort and total cost requirements. Local Government Unit to support through grants and funding the local rice farmers in maximizing utilization of machines that shows positive effect.